Eudorylaimus species (Nematoda: Dorylaimida) of continental Antarctica (Journal of Nematode Morphology and Systematics, 2012)
Six Eudorylaimus species living on Antarctic mainland are described and compared on the basis of paratype or freshly collected specimens. They are: E. antarcticus (Steiner, 1916) Yeates, 1970, E. nudicaudatus Heyns,1993, E. shirasei Kito, Shishida & Ohyama, 1996, E. glacialis Andrassy, 1998, E. quintus sp. n. and E. sextus sp. n. Of the two new species, E. quintus can be di stinguished from the other fi ve particularly by the unusually large intestinal vacuola and the greater number of the male supplements (9–11 vs 6–9), and E. sextus by the twisted anterior end and the posterior position of the dorsal pharyngeal nucleus. A key to the six species is added.